Architecting the e-RES (Electric Bike Rescuer) Application Based on Microservices Architecture - Ismail, Jefri Abdurrozak (Information Technology International Journal, 2025)
The e-RES application is a solution designed to assist electric bike riders facing technical issues on the road. Utilizing mobile technology and a microservices-based architecture, this app enables riders to connect instantly with nearby technicians in real-time. This journal discusses the architecting process of e-RES, including system architecture design and preparation of essential diagrams such as a Use Case Diagram, Class Diagram, Sequence Diagram, Activity Diagram, and Entity Relationship Diagram.